Development of alkali activated cements and concrete mixture design with high volumes of red mud. (1st October 2017) - Krivenko, Pavel; Kovalchuk, Oleksandr; Pasko, Anton; Croymans, Tom; Hult, Mikael; Lutter, Guillaume; Vandevenne, Niels; Schreurs, Sonja; Schroeyers, Wouter
Highlights: The AAC with red mud content 80% and concrete (red mud content 90%) were designed. Compressive strength could reach 60 MPa for cements and 70 MPa for concrete. Hydration products are calcium silicate hydrates, klinoferrosilite, lawsonite. From the radiological point of view materials could be used for road construction. Abstract: Dedicated cement compositions were formulated to enable the incorporation of large volume fractions of red mud in alkali activated cements, taking into account the role of the aluminosilicate phase in the processes of hydration and hardening. High volume red mud alkali activated cements were synthesized using a proper combination of red mud, low basic aluminosilicate compounds with a glass phase (blast-furnace slag) and additives selected from high-basic Ca-containing cements with a crystalline structure (Portland cement). Compressive strength of the cements under study is 30–60 MPa (tested in mortar). The microstructure of the hardened cement paste and the role of red mud in the structure formation process were investigated. In addition to the use of red mud in cement, its use as an aggregate in concrete was studied to enable the use of larger quantities in the final concrete. In concrete road bases, the use of red mud can reach even 90% by mass. Since enhanced concentrations of naturally occurring radionuclides can be present in red mud this aspect was investigated to make sure that these materials are safe to use from a radiological point of view.